Strategic delegation and voting rules - Bård Harstad (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 2007)
When making collektive desicions, principals (voters or districts) typically benefit by strategically delegating their bargaining and voting power to representatives different from themselves. There are conflicting views in the literature, however, of whether such a delegate should be conservative (status quo biased) or instead progressive relative to his principal. I show how the answer depends on the political system in general, and the majority requirement in particular. A larger majority requirement leads to conservative delegation, but sincere delegation is always achieved by the optimal voting rule.
Keywords: D71; D72; F53; H11; 330; Strategic delegation; collective decisions; voting rules; Abstimmungsregel; Public Choice; Wahlverhalten